Comparison between cardiac output values measured by thermodilution and partial carbon dioxide rebreathing in patients with acute lung injury - Valiatti, Jorge Luís dos Santos; Amaral, José Luiz Gomes do (São Paulo Medical Journal, 2004)
CONTEXT: Thermodilution, which is considered to be a standard technique for measuring the cardiac output in critically ill patients, is not free from relevant risks. There is a need to find alternative, noninvasive, automatic, simple and accurate methods for monitoring cardiac output at the bedside. OBJECTIVE: To compare cardiac output measurements by thermodilution and partial carbon dioxide rebreathing in patients with acute lung injury at two levels of severity (lung injury score, LIS: below 2.5, group A; and above 2.5, group B). TYPE OF STUDY: Comparative, prospective and controlled study. SETTING: Intensive Care Units of two university hospitals. METHODS: Cardiac output was measured by thermodilution and partial carbon dioxide rebreathing. Twenty patients with acute lung failure (PaO2/FiO2 < 300) who were under mechanical ventilation and from whom 294 measurements were taken: 164 measurements in group A (n = 11) and 130 in group B (n = 9), ranging from 14 to 15 determinations per patient. RESULTS: There was a poor positive correlation between the methods studied for the patients from groups A (r = 0.52, p < 0.001) and B (r = 0.47, p < 0.001). The application of the Bland-Altman test made it possible to expose the lack of agreement between the methods (group A: -0.9 ± 2.71 l/min; 95% CI = -1.14 to -0.48; and group B: -1.75 ± 2.05 l/min; 95% CI = -2.11 to -1.4). The comparison of the results (Student t and Mann-Whitney tests) within each group and between the groups showed significant difference (p = 0.000, p < 0.05). DISCUSSION: Errors in estimating CaCO2 (arterial CO2 content) from ETCO2 (end-tidal CO2) and situations of hyperdynamic circulation associated with dead space and/or increased shunt possibly explain our results. CONCLUSION: Under the conditions of this study, the results obtained allow us to conclude that, in patients with acute lung injury, the cardiac output determined by partial rebreathing of CO2 differs from the measurements obtained by thermodilution. This difference becomes greater, the more critical the lung injury is.